Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Let's solve the given system of linear equations step by step:
1. The system of equations is:
[tex]\[ \begin{cases} 2x + y + z = 92 \\ x + 2y + z = 8 \end{cases} \][/tex]
2. Let's isolate one of the variables from one of the equations. For simplicity, we will work with the first equation to express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] and [tex]\( z \)[/tex]:
[tex]\[ 2x + y + z = 92 \implies y = 92 - 2x - z \][/tex]
3. Substitute the expression for [tex]\( y \)[/tex] from the first equation into the second equation:
[tex]\[ x + 2(92 - 2x - z) + z = 8 \][/tex]
Simplify and solve the resulting equation step by step:
[tex]\[ x + 184 - 4x - 2z + z = 8 \\ x - 4x + 184 + z - 2z = 8 \\ -3x + 184 - z = 8 \][/tex]
[tex]\[ -3x - z = -176 \\ z = -3x + 176 \][/tex]
4. Now, we have found expressions for [tex]\( y \)[/tex] and [tex]\( z \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ y = 92 - 2x - z \\ y = 92 - 2x - (-3x + 176) \][/tex]
Simplify the above:
[tex]\[ y = 92 - 2x + 3x - 176 \\ y = x - 84 \][/tex]
5. Therefore, the generalized solutions based on the discovered relationships are:
[tex]\[ x = x \\ y = x - 84 \\ z = 176 - 3x \][/tex]
Based on this analysis, the solution set for the given system of equations can be written as:
[tex]\[ \left\{\begin{array}{l} x = x \\ y = x - 84 \\ z = 176 - 3x \end{array}\right. \][/tex]
6. To find a specific solution, we can assume a value for one of the variables. Let's assume [tex]\( z = 0 \)[/tex].
[tex]\[ 176 - 3x = 0 \implies 3x = 176 \implies x = \frac{176}{3} \][/tex]
7. Substitute [tex]\( x = \frac{176}{3} \)[/tex] back into the equation for [tex]\( y \)[/tex]:
[tex]\[ y = x - 84 \implies y = \frac{176}{3} - 84 \][/tex]
[tex]\[ y = \frac{176}{3} - \frac{252}{3} = \frac{176 - 252}{3} = \frac{-76}{3} \][/tex]
So, the specific solution set with [tex]\( z = 0 \)[/tex] is:
[tex]\[ \left\{\begin{array}{l} x = \frac{176}{3} \\ y = \frac{-76}{3} \\ z = 0 \end{array}\right. \][/tex]
Thus, the generalized solution to the system of equations is:
[tex]\[ x = \frac{176}{3} - \frac{z}{3}, \quad y = \frac{-76}{3} - \frac{z}{3} \][/tex]
and a specific solution for [tex]\( z = 0 \)[/tex] is:
[tex]\[ x = \frac{176}{3}, \quad y = \frac{-76}{3}, \quad z = 0 \][/tex]
1. The system of equations is:
[tex]\[ \begin{cases} 2x + y + z = 92 \\ x + 2y + z = 8 \end{cases} \][/tex]
2. Let's isolate one of the variables from one of the equations. For simplicity, we will work with the first equation to express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] and [tex]\( z \)[/tex]:
[tex]\[ 2x + y + z = 92 \implies y = 92 - 2x - z \][/tex]
3. Substitute the expression for [tex]\( y \)[/tex] from the first equation into the second equation:
[tex]\[ x + 2(92 - 2x - z) + z = 8 \][/tex]
Simplify and solve the resulting equation step by step:
[tex]\[ x + 184 - 4x - 2z + z = 8 \\ x - 4x + 184 + z - 2z = 8 \\ -3x + 184 - z = 8 \][/tex]
[tex]\[ -3x - z = -176 \\ z = -3x + 176 \][/tex]
4. Now, we have found expressions for [tex]\( y \)[/tex] and [tex]\( z \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ y = 92 - 2x - z \\ y = 92 - 2x - (-3x + 176) \][/tex]
Simplify the above:
[tex]\[ y = 92 - 2x + 3x - 176 \\ y = x - 84 \][/tex]
5. Therefore, the generalized solutions based on the discovered relationships are:
[tex]\[ x = x \\ y = x - 84 \\ z = 176 - 3x \][/tex]
Based on this analysis, the solution set for the given system of equations can be written as:
[tex]\[ \left\{\begin{array}{l} x = x \\ y = x - 84 \\ z = 176 - 3x \end{array}\right. \][/tex]
6. To find a specific solution, we can assume a value for one of the variables. Let's assume [tex]\( z = 0 \)[/tex].
[tex]\[ 176 - 3x = 0 \implies 3x = 176 \implies x = \frac{176}{3} \][/tex]
7. Substitute [tex]\( x = \frac{176}{3} \)[/tex] back into the equation for [tex]\( y \)[/tex]:
[tex]\[ y = x - 84 \implies y = \frac{176}{3} - 84 \][/tex]
[tex]\[ y = \frac{176}{3} - \frac{252}{3} = \frac{176 - 252}{3} = \frac{-76}{3} \][/tex]
So, the specific solution set with [tex]\( z = 0 \)[/tex] is:
[tex]\[ \left\{\begin{array}{l} x = \frac{176}{3} \\ y = \frac{-76}{3} \\ z = 0 \end{array}\right. \][/tex]
Thus, the generalized solution to the system of equations is:
[tex]\[ x = \frac{176}{3} - \frac{z}{3}, \quad y = \frac{-76}{3} - \frac{z}{3} \][/tex]
and a specific solution for [tex]\( z = 0 \)[/tex] is:
[tex]\[ x = \frac{176}{3}, \quad y = \frac{-76}{3}, \quad z = 0 \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.